Water Productivity Atlas: Closing key gaps in assessment metrics to enhance cross-sector benefits - Amarasinghe, Upali A.; Perera, Madhusha; Sikka, Alok; Panda, Rabindra, K.; Sarangi, Arjamadutta; Lautze, Jonathan F.; Ghosh, Surajit (CGIAR, 2024)
The Water Productivity Atlas, developed by IWMI in partnership with the Indian Council of Agricultural Research, is a one-stop shop for visualizing the water productivity and water footprints of different crops, cropping patterns, and agricultural systems